“Mirror of Identity”; Political Personalization of French Presidential Candidates in Mass Media - Aprillia Firmonasari (UIN Salatiga, 2021)
EnglishThe development of political communication has brought various interactional communicative strategies among political participants, namely: politicians, journalists and the public. This strategy mainly emerged during the presidential campaign, due to at this time the presidential candidates are competing to win votes. One of the ways to obtain high votes is through political personalization. This identification process is carried out with the help of mass media, which framed the individuality actions of the presidential candidates in various ways. This study analyzes French media framing toward political personalization by Emmanuel Macron (EM) and Marine Le Pen (MLP). Data collection was carried out with the help of NVIVO’s linguistic tools to see trend in lexical forms and lingual expressions used by the media and social media. This research is expected to become a discourse analysis research model based on the interactional system between participants in French politics, particularly those related to national identity.